The general situation of Covid-19 in Iraq - Hussain, Eman Mohammed; Awad, Hussein Kamil; Ibadi, Emam Atiyah (Journal of agricultural, environmental and veterinary sciences, 2024)
The Coronavirus has caused the death of nearly five million people, according to data provided by the World Health Organization. In Iraq, in February 2020, the first confirmed cases of infection were announced, and it raised great concern due to the primitive health infrastructure. SARS-CoV-2 is a beta coronavirus belonging to the subgenus Sarbecovirus. The epidemic led to the loss of human lives that prompted the world to be cautious and fearful of the future, because due to the strength and ferocity of the virus, some factors that increased the severity of the disease, including weak immunity caused by some diseases like cancer. The respiratory system is the main target of the virus, but due to the systemic nature of the disease, the inflammatory condition may generalize and affect the rest of the body’s organs. Some methods have emerged aimed at stopping the chain of this epidemic, including social distancing and the use of sterilizers, but these measures are considered primitive when compared to the ferocity of the virus. Many research centers and scientists cooperated to find a suitable vaccine for the virus. In the beginning, companies used old methods to produce the vaccine, such as using parts of viruses and injecting them into the host. From here, companies began racing in a scientific way to find the appropriate vaccine. This review, discussed the health situation within Iraqi society regarding the Corona virus since the first infection was recorded. also discussed the targeted organs, the impact of diseases on the virus, and the vaccines used. We conclude that awareness is an important factor in avoiding global epidemics, which is represented by adhering to preventive measures and taking vaccines, as it has not become clear that the Corona virus is a seasonal virus, but rather what helps in its spread are the health conditions of the host, specifically the condition of the lungs.